2009
DOI: 10.1111/j.1758-5910.2009.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic obesity surgery in an Asian Institute: A 10‐year prospective study with review of literature

Abstract: Objective: Obesity surgery is the most effective treatment for morbid obesity and leads to dramatic improvement in related co-morbidities. The aim of this study was to present the long-term results of a prospective trial studying the efficacy of laparoscopic obesity surgery in a group of oriental patients. patients who underwent obesity surgery in a single bariatric center in Asia were recruited. Various procedures have been adopted so far, including laparoscopic vertical banded gastric partition in 652 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Our findings are similar with data from a study in the United States that reported a higher rate of utilization of the minimally invasive bariatric surgery among higher SES patients and those with private insurance [ 19 ]. Most patients treated with minimally invasive approach because of smaller incisions and quicker recovery [ 2 , 3 ]. In addition, morbidly obese patients who had undergone bariatric surgery typically had multiple obesity-related comorbidities that might have substantially increased their surgical risk [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our findings are similar with data from a study in the United States that reported a higher rate of utilization of the minimally invasive bariatric surgery among higher SES patients and those with private insurance [ 19 ]. Most patients treated with minimally invasive approach because of smaller incisions and quicker recovery [ 2 , 3 ]. In addition, morbidly obese patients who had undergone bariatric surgery typically had multiple obesity-related comorbidities that might have substantially increased their surgical risk [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bariatric surgery has been proven as an attractive and effective control method for morbid obesity and associated metabolic disorders [ 1 , 2 ]. With the development of advanced surgical instrumentation and introduction, the numbers of laparoscopic bariatric procedures have grown substantially in developed and developing countries in the past decade [ 3 5 ]. In Taiwan, the annual number of bariatric surgery cases, particularly laparoscopic bariatric surgery (LBS), has increased over the past few years [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Asia, LAGB has been performed in Singapore and Taiwan since 1999 (11,12), but to our knowledge, few intermediate-or long-term results have been reported in the English-language literature until now. Lee et al from Taiwan only recently reported their 5-year data (13). In Japan, Kasama et al first reported data on LAGB with the LAP-BAND system in English (14), but their data only covered up to 18 months of follow-up and reported a high complication rate (30.8%).…”
Section: Discussionmentioning
confidence: 99%